When she dreams [large type] - Quick, Amanda (Quick, Amanda. Burning Cove, 2022)
"Maggie Lodge, assistant to the advice columnist known only as Dear Aunt Cornelia to her readers, hires private eye Sam Sage to help track down the person who is blackmailing her employer. Maggie and Sam are a mismatched pair. As far as Sam is concerned, Maggie is reckless and in over her head. She is not what he had in mind for a client, but he can't afford to be choosy. Maggie, on the other hand, is convinced that Sam is badly in need of guidance and good advice. She does not hesitate to give him both. In spite of the verbal fireworks between them, they are fiercely attracted to each other, but each is convinced it would be a mistake to let passion take over. hey are, after all, keeping secrets from each other. Sam is haunted by his past, which includes a marriage shattered by betrayal and violence. Maggie is troubled by intense and vivid dreams--dreams that she can sometimes control. There are those who want to run experiments on her and use her for their own purposes, while others think she should be committed to an asylum. When the pair discovers someone is impersonating Aunt Cornelia at a conference on psychic dreaming and a woman dies at the conference, the door is opened to a dangerous web of blackmail and murder. Secrets are revealed, leaving Maggie and Sam in the path of a ruthless killer who will stop at nothing to exact vengeance"--